Study The Potential Fisheries Fish Terubuk ( Tenualosa Macrura ) In Waters Bengkalis Riau - Eko Purwanto; Alit Hindri Yani; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in August and November 2013 in the province of Riau Strait Bengkalis. The method used in this study is a survey method . The purpose of this study was to determine the potential catches Terubuk ( Tenualosa macrura ) in Bengkalis waters. The results showed that the results of the survey of the Terubuk fish were caught fishing waters Bengkalis the month from August to November 2013. Retrieved Terubuk number and size of fish caught as many as 3554 head comprising 1082 males and 2472 Terubuk tail tail Terubuk females . Terubuk fish growth speed at the time a young age faster than when the fish is old. The rapid growth of the young - old fish occurs because the energy obtained from food are mostly used for growth. In older fish the energy obtained from food is no longer used for growth, but only used to maintain it self and replace the damaged cells.The rate of death arrest ( F ) during the study period is higher than the rate of natural mortality ( M ) , so that the total mortality rate ( Z ) during the periods of the study are determined by the rate of death arrest ( F ). Terubuk fish mortality rate during the study period due to factors at the time of capture by fishing for migratory fish spawning . Terubuk endangered fish caused by two main factors : first, the seizure at the time of entry into migratory fish Strait Bengkalis, secondly, the quality of the water into a fish alive Terubuk diminishing.Keywords : Potential , Terubuk Fish , Aquatic Bengkalis